2017
DOI: 10.3126/jkmc.v5i2.18409
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of prehypertension in mothers of young children in peri-urban Nepal

Abstract: Background: Prehypertension is clinically defi ned as a level of blood pressure between normal and hypertension, i.e. elevated systolic blood pressure between120-139 or diastolic blood pressure between 80-89 mm Hg. Prehypertension remains neglectedas a public health problem, and has not been explored in mothers with small childrenin Nepal. Objectives: We aimed to study prehypertensionand its related factors including obesity-related parameters among mothers with children aged 1-7 years in Duwakot and Jhaukhel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Our earlier studies in the Jhaukhel-Duwakot Health Demographic Surveillance Site (JD-HDSS) in the Bhaktapur district near Kathmandu, Nepal's capital city [17], showed a high prevalence of CVD risk factors, including unhealthy diet and low physical activity [18,19]. JD-HDSS also showed a high prevalence of prehypertension (31.8%) in mothers of young children [20]. Further, our qualitative study among mothers in JD-HDSS revealed gaps and misconceptions regarding heart-healthy diet and physical activity [21].…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier studies in the Jhaukhel-Duwakot Health Demographic Surveillance Site (JD-HDSS) in the Bhaktapur district near Kathmandu, Nepal's capital city [17], showed a high prevalence of CVD risk factors, including unhealthy diet and low physical activity [18,19]. JD-HDSS also showed a high prevalence of prehypertension (31.8%) in mothers of young children [20]. Further, our qualitative study among mothers in JD-HDSS revealed gaps and misconceptions regarding heart-healthy diet and physical activity [21].…”
Section: Introductionmentioning
confidence: 99%